High-Protein Weight Loss Diets and Purported Adverse Effects: Where is the Evidence? - Manninen Anssi H (Taylor & Francis Group, 2004)
Abstract Results of several recent studies show that high-protein, low-carbohydrate weight loss diets indeed have their benefits. However, agencies such as the American Heart Association (AHA) have some concerns about possible health risks. The purpose of this review is to evaluate the scientific validity of AHA Nutrition Committee's statement on dietary protein and weight reduction (St. Jeor ST et al. Circulation 2001;104:1869-1874), which states: "Individuals who follow these [high-protein] diets are risk for ... potential cardiac, renal, bone, and liver abnormalities overall. Simply stated, there is no scientific evidence whatsoever that high-protein intake has adverse effects on liver function. Relative to renal function, there are no data in the scientific literature demonstrating that healthy kidneys are damaged by the increased demands of protein consumed in quantities 2-3 times above the Recommended Dietary Allowance (RDA). In contrast with the earlier hypothesis that high-protein intake promotes osteoporosis, some epidemiological studies found a positive association between protein intake and bone mineral density. Further, recent studies studies suggest, at least in the short term, that RDA for protein (0.8 g/kg) does not support normal calcium homeostasis. Finally, a negative correlation has been shown between protein intake and systolic and diastolic blood pressures in several epidemiological surveys. In conclusion, there is little if any scientific evidence supporting above mentioned statement. Certainly, such public warnings should be based on a thorough analysis of the scientific literature, not unsubstantiated fears and misrepresentations. For individuals with normal renal function, the risks are minimal and must be balanced against the real and established risk of continued obesity.